Carbon Dots for Photocatalytic Degradation of Aqueous Pollutants: Recent Advancements. Issue 17 (3rd June 2021) - Akbar, Kamran; Moretti, Elisa; Vomiero, Alberto
Abstract: The immense progress of humanity on the technological, domestic, and industrial fronts comes at the cost of polluting the planet. Aquatic pollution is particularly dangerous since all life forms are directly linked to it. Each year tons of industrial and domestic pollutants make their way into aqueous systems. Efficient removal/degradation of these pollutants is of prime importance for the sustainable future. Among many technologies, photodegradation is an emerging and promising method for the successful removal of aqueous pollutants since it is powered by abundant solar light. The last decade had shown that carbon dots are among the most promising materials that can be utilized as an efficient tool to derive various solar‐driven chemical reactions. Carbon dots possess unique photophysical and chemical properties such as light‐harvesting over a broad‐spectrum region, upconversion photoluminescence, photosensitizers, chemical inertness, and bivalent redox character, etc. The ease of synthesis of carbon dots at low cost also contributes hugely to their utilizations as an efficient photocatalyst for the degradation of aqueous pollutants. This review summarizes the recent progress made in the field of photodegradation of aqueous pollutants with the aid of carbon dots and their hybrids, highlighting the critical role carbon dots can play in the field. Abstract : Aqueous pollutants pose serious threats to the environment. Degradation of these pollutants via photocatalysis is an emerging strategy because it utilizes abundant solar energy. Carbon dots possess unique photophysical and chemical properties rendering them a promising material for photodegradation of aqueous pollutants. This review summarizes the recent progress in the field of photodegradation of aqueous pollutants through application of carbon dots and their hybrids.